Rehabilitation Therapy Utilization in Patients with Parkinson’s Disease in Korea - Han Gil Seo; Sang Jun Park; Jiah Seo; Seong Jun Byun; Byung-Mo Oh (Parkinson's Disease)
Objective. Although evidence and guidelines recommend appropriate rehabilitation from the beginning of diagnosis in patients with Parkinson’s disease (PD), there is a lack of data addressing the utilization of rehabilitation therapies for these patients in practice. The aim of this study is to investigate the rate of rehabilitation therapy utilization over time in patients with PD using a nationwide cohort in Korea. Methods. Patients were identified using the registration code for PD in the program for rare, intractable disease from the National Health Insurance Service-National Sample Cohort database, which consists of 979,390 Korean residents. Data were divided into four periods: 2004–2006, 2007–2009, 2010–2012, and 2013–2015. We assessed the utilization of rehabilitation therapies and the associated patient characteristics. Results. The numbers of patients with PD were 384 in 2004, 855 in 2007, 1,023 in 2010, and 1,222 in 2013. The numbers of physiatrist visits per person were 0.58, 0.96, 1.97, and 2.91, in the respective periods. Among the patients, 35–40% had claims for physical therapy, 16–19% for occupational therapy, and 4–6% for swallowing therapy. There were no remarkable differences between these rates between the study periods. Sex, age, income, disability, and levodopa-equivalent dose were significantly associated with the utilization of rehabilitation therapy. Conclusion. This study demonstrated that the rate of rehabilitation therapy utilization did not change remarkably in patients with PD from 2004 to 2015 in Korea although the number of physiatrist visits increased dramatically. The present evidence and guidelines may have not been adequately integrated into clinical practice during the period of study. Additional efforts may be warranted to provide adequate rehabilitation therapies in clinical practice for patients with PD.